The Development of Make a Match Card Learning Media on Animal Tissue Material to Improve Cognitive Learning Results - Zaida Fithrotul Ilma; Raharjo Raharjo; Firas Khaleyla (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2022)
The education system is defined as a process of learning something new, where the process can develop the potential within and then increase student interest in learning Increasing students' learning interest will have a good impact on teaching and learning activities so that learning results can be achieved. The learning that has been carried out so far seems to be still less than optimal, while students are required to master all existing concepts, especially on Animal Tissue material. In addition, the lack of optimal learning media is one of the reasons why student learning results’ decline. For that, it takes a learning media that can act as a bridge to understanding the concepts. The purpose of this research was to describe the level of effectiveness and practicality of using the Make a-Match cards on Animal Tissue material. This research was quantitative descriptive research. The model used was ASSURE with six stages. This study used a one group pretest-posttest design. The trial was carried out at XI MIPA 4 SMAN 8 Surabaya. Research instruments included test sheets, validation, observation, and student responses. The results showed that the completeness indicator scores 75% in the complete category, validation scores 79.3% in the valid category, the implementation observation was 100% in the very good category, and student responses were 94.5% in the very practical category. Thus, the Make a-Match Card learning media can be used for the learning process at school.